METTL16-dependent miR-146b-5p m6A modification remodeling sensitize NSCLC to osimertinib via activating PI3K/AKT signaling - Hongyang Sang; Jinlong Liu; Xifang Chen; Yingou Zeng (BMC Cancer)
Abstract Background Non-small-cell lung cancer (NSCLC) is one of the most common malignant tumors, with poor prognosis and increasing osimertinib therapy resistance. Revealing mechanisms of NSCLC progression and therapy resistance remains critical. The aim of this study was to elucidate the molecular mechanism of miR-146b-5b-5p m6A modification and underlying function in regulating the proliferation and osimertinib resistance of NSCLC. Methods TCGA, GEO datasets were used to analyze the differential expression of miR-146b-5p in NSCLC and adjacent tissues, and its impact on prognosis. Then the effects of miR-146b-5p on the proliferation and osimertinib of A549 and HCC827 cells were investigated through proliferation experiments, colony formation assay and IC50 assay. The regulatory mechanism of miR-146b-5p on the PI3K/AKT signaling pathway and its interaction in cancer progression were investigated through Western blots, dual-luciferase reporter assay, and rescue experiments. Results miR-146b-5p was significantly upregulated in NSCLC tissue and represented worse prognosis. miR-146b-5p mimic significantly enhanced proliferation and osimertinib resistance, while miR-146b-5p inhibitor inhibited above phenotype. Through bioinformatic analysis and experimental results, miR-146b-5p interacted directly with PTEN mRNA and activated subsequent signaling pathway activation. PI3K/AKT inhibitor could eliminate the tumorigenic effects of miR-146b-5p mimic on the progression of NSCLC, while PI3K/AKT agonist could rescue the inhibition effect of miR-146b-5p inhibitor group cells. Further, methyltransferase METTL16 is responsible for miR-146b m6A modification. Modified miR-146b-5p promotes osimertinib resistance through downstream PI3K/AKT activation. Conclusions In summary, we found that METTL16 mediated miR-146b-5p m6A modification promoted the proliferation and osimertinib resistance of NSLCL by activating PI3K/AKT signaling pathway. Our study is expected to provide a novel insight and potential therapeutic target for NSCLC osimertinib resistance.